PENGARUH DEWAN KOMISARIS INDEPENDEN, UKURAN KOMITE AUDIT, KEAHLIAN KOMITE AUDIT, RAPAT KOMITE AUDIT, RAPAT DEWAN PENGAWAS SYARIAH TERHADAP AUDIT REPORT LAG (Studi Empiris pada perbankan syariah yang terdaftar di OJK Tahun 2016-2020) - Dzulkifli Dzulkifli; Totok Dewayanto (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to examine the extent of audit report lag and its association with governance mechanisms in the Islamic banking institutions in Indonesia. The dependent variable in the study is audit report lag which is measured based on the period starting from the deadline for the company to close its books on December 31 to the date specified in the independent auditor's report. The sample of the study comprises 120 observations of Islamic banking institutions’ financial reports for the period 2016-2020 using purposive sampling technique. The method that used to test the hypothesis is multiple linear regression analysis. The analysis results show that the size of the board of commissioners independent, audit committee size, audit committee expertise, and sharia supervisory board meetings have no effect on audit report lag. While the audit committee meeting has significant effect.